Secrecy strategies: Global patterns in elites’ quest for confidentiality in offshore finance - Ho-Chun Herbert Chang; Brooke Harrington; Daniel Rockmore (PLoS ONE, 2025)
Scholars and policy-makers know a lot about the ways offshore financial centers compete with one another to offer secrecy to elites, but still know too little about how and why elites take up these offerings to conceal their assets and identities offshore. This paper fills the gap in knowledge by examining the distinct patterns for achieving offshore secrecy among elites in 65 countries. We take a cross-national comparative perspective, showing that the patterns are contingent in part on political conditions in the elites’ home countries. Using data from two publicly available sources— the Offshore Leaks Database and the World Justice Project Rule of Law Index—we advance knowledge for scholars and policy-makers with three main results. First, we find that elites from corrupt countries are more likely to spread their assets across multiple offshore financial centers: they diversify across the system, instead of putting all their eggs in one basket. Second, countries where the risk of government confiscation of private assets is high—either due to lack of civil rights or very effective law enforcement—elites make heavy use of identity-concealing offshore strategies such as bearer instruments and nominees to shield their names from discovery in public records. Third, elites from countries where both corruption and confiscation pose significant risks make extensive use of blacklisted offshore financial centers, despite the reputational and practical risks that entails for them. All three patterns achieve secrecy, but through different means; our findings have implications for public policy, as well as for models of inequality, elites, and financial crime.